Development Web Based Employment Information System for Yugo Putra Sejahtera Inc. - Nur Alan Setiawan; Budi Rachmadani; Emil Riza Putra (Politeknik Pertanian Negeri Samarinda, 2022)
This research is based on Yugo Putra Sejahtera Inc. is a company engaged in distributors, in the processing of letters in the personnel section it is still done manually starting from the manufacturing stage to the stage of sending and receiving the letter. The purpose of this research is to create a personnel information system at pt. Yugo Putra Prosperity is web-based using the Laravel Framework programming language and MySQL as the database. The results of this study indicate that the trials produced on the respondent's test indicate that the application used can present mail data information and optimize the online correspondence process properly.